Depth-resolved X-ray magnetic circular dichroism measurement by a multi-anode microchannel plate detector combined with polarization switching. (May 2016) - Amemiya, K; Sakamaki, M; Kishimoto, S; Kosuge, T; Nigorikawa, K; Tanaka, M; Uchida, T; Saito, M; Ikeno, M; Nakayoshi, K
Abstract: A depth-resolved X-ray magnetic circular dichroism (XMCD) technique has been developed in the soft X-ray region by combining a multi-anode microchannel plate detector with polarization switching between right and left circular polarizations. A simultaneous measurement for 30-channel anodes has been achieved with a continuous data acquisition rate of 1 kHz, which is fast enough for 10 Hz polarization switching. This enables us to realize the layer-resolved XMCD analysis with a high signal-to-noise ratio.